Trait Anxiety and Fictional Exposure: How Movie Preferences Shape Psychological Resilience and Pandemic Preparedness - Dar, Kaneez Fatima; Asthana, Manish Kumar (Utan Kayu Publishing, 2025)
People differ in their ability to cope with stressful situations. The pandemic outbreak put the world under a lot of stress and challenges in the form of its prevention and its repercussions. People with different levels of trait anxiety cope differently with stressful situations. This study examines the association of trait anxiety with pandemic psychological resilience and pandemic preparedness. People around the world enjoy engaging with fictional experiences. One reason why people enjoy such experiences is that they provide people with simulations of real events that can act as a source of information. The current study investigated the relationship between movie genres and psychological resilience and preparedness towards the pandemic. We conducted an online study with 120 participants, mean age (SD) =18.36 (.73) years. The data was collected through convenience and snowball sampling methods. The participants filled out demographic questionnaires, State-Trait Anxiety questionnaire, Emotion Regulation Questionnaire, movie genre preference questionnaire, pandemic psychological resilience scale, and pandemic preparedness scale. The results indicated a negative interaction between trait anxiety and cognitive reappraisal, a positive interaction between trait anxiety and positive resilience, and a positive interaction between trait anxiety and psychological distress towards the pandemic. Our results showed that certain movie genre preferences are significantly correlated with positive resilience and psychological distress towards the pandemic.